Enhanced room-temperature hydrogen storage in super-activated carbons: The role of porosity development by activation - Xia, Kaisheng; Hu, Juan; Jiang, Jinhua (Applied surface science, 2014)
•Synthesis of super-activated carbons by combining template method with activation.•The effect of activation on porosity development of as-prepared carbons is studied.•Super-activated carbons demonstrate enhanced room-temperature hydrogen storage.•Increase of pores around 1.2nm is essential for the enhanced H2 uptake at 298K. Efficient hydrogen storage with a high density under near-ambient temperature remains a key technical obstacle for a hydrogen economy. Here we demonstrate the enhanced room-temperature hydrogen storage in super-activated carbon materials, which were prepared by carbon dioxide activation of templated porous carbons. These carbon materials possess high specific surface areas of up to 2829m2/g, large pore volumes of up to 2.34cm3/g, and hierarchical pore structures consisting of primary micropores with median size in the range of 0.7–1.3nm and secondary mesopores with the size of 2–4nm. One of the super-activated carbons exhibits a high hydrogen uptake of 0.95wt% at 298K and 80bar, which is among the highest data reported for the porous carbon materials at room temperature and moderate pressure. The role of porosity development caused by activation in improving the hydrogen storage properties of the carbon materials has been investigated. A close relationship between hydrogen storage capacities and micropore volumes has been found. The microporosity development, especially the rapid increase of narrow pores with the diameters around 1.2nm, appears to be essential for the enhanced room-temperature hydrogen storage in the super-activated carbons.